ASESMEN KOMPETENSI MINIMUM SEBAGAI TRANSFORMASI PENDIDIKAN DI SEKOLAH DASAR - Adnan Musafa Hanafi; Minsih Minsih (Kwangsan: Jurnal Teknologi Pendidikan, 2022)
In 2021, the government issued a new policy, namely the "Merdeka Belajar" program to improve the quality of education in Indonesia. The quality of education can be improved through the development of student literacy and numeracy skills with the Minimum Competency Assessment (AKM), which is a national assessment instrument that tests students' reading and numeracy literacy skills. Through Minimum Competency Assessment (AKM), the transformation of education in Indonesia is expected to be more creative and innovative. This research is of the qualitative research type with a case study approach. This study involved the principal, grade 5th teacher, and three grade 5th students of Elementary School 2 Lemahireng who were selected by the snow-ball sampling technique. The research instrument is in the form of interview guidelines. Data collection uses observation, interview, and documentation techniques. Data analysis uses reduction, data presentation, and conclusion techniques. In this study, source triangulation was used. The results showed that school preparation in facing Minimum Competency Assessment (AKM) includes providing facilities and infrastructure, conducting training for teachers, and equipping students with tryouts. School obstacles in implementing Minimum Competency Assessment (AKM) are not stable internet network, insufficient number of learning modules, teachers applying lecture methods, at least preparation time, difficulty in developing assessments and compiling Minimum Competency Assessment (AKM)-based questions, and some students who are not good at reading. AbstrakPada tahun 2021, pemerintah mengeluarkan kebijakan baru yaitu program “Merdeka Belajar” untuk memperbaiki mutu pendidikan di Indonesia. Mutu pendidikan dapat ditingkatkan melalui pengembangan kemampuan literasi dan numerasi siswa dengan Asesmen Kompetensi Minimum (AKM), yang merupakan suatu instrumen asesmen nasional yang menguji kemampuan literasi membaca dan numerasi siswa. Melalui AKM, transformasi pendidikan di Indonesia diharapkan dapat lebih kreatif dan inovatif. Penelitian ini berjenis penelitian kualitatif dengan pendekatan studi kasus. Penelitian ini melibatkan kepala sekolah, guru kelas 5, dan tiga siswa kelas 5 SD Negeri 2 Lemahireng yang dipilih dengan teknik snow-ball sampling. Instrumen penelitian berupa pedoman wawancara. Pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Analisis data menggunakan teknik reduksi, penyajian data, dan menyimpulkan. Pada penelitian ini digunakan triangulasi sumber. Hasil penelitian menunjukkan bahwa persiapan sekolah dalam menghadapi AKM meliputi, penyediaan sarana dan prasarana, mengadakan pelatihan bagi guru, serta membekali siswa dengan tryout. Kendala sekolah dalam pelaksanaaan AKM, yaitu belum stabilnya jaringan internet, jumlah modul pembelajaran belum mencukupi, guru menerapkan metode ceramah, sedikitnya waktu persiapan, kesulitan guru dalam mengembangkan penilaian dan menyusun soal berbasis AKM, dan beberapa siswa yang belum pandai membaca.